Efforts to Overcome Illegal Fishing Practices as a form of Criminal Action in The Economic Field - Eva - Arief; Siti Mariyam (Faculty of Law, Universitas Pekalongan, 2024)
Indonesia is an archipelago with a larger water area than land, which produces abundant marine wealth which is a strategic potential for national economic development. Geo-politically, Indonesia has a very strategic role because it is located between the Asian continent and the Australian continent, as well as the Pacific and Indian oceans, placing Indonesia as the world's maritime axis in the context of global trade connecting the Asia-Pacific region with Australia. Indonesia is often faced with various security issues and violations of the law in Indonesia's marine territory, including illegal fishing, which causes significant losses. Illegal fishing is a form of illegal action that can have an impact on the country's economy. Therefore, illegal fishing can be qualified as an economic crime. Illegal fishing can be classified as property crimes because its existence clearly threatens the safety of the State's property or wealth. Thus, the qualification as an economic crime is more on the basis of consideration of the consequences/loss caused to the state economy.